POTENSI BIOAKTIVITAS KURKUMIN DENGAN NANOENKAPSULASI KITOSAN SEBAGAI PENDEKATAN HOST-DIRECTED THERAPY HERBAL MUTAKHIR PADA TUBERKULOSIS DI INDONESIA: Pemanfaatan Herbal sebagai Terapi Adjuvan pada Penyakit Infeksi Bergantung Antibiotik - Athoillah, Nabil (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2024)
Background: Tuberculosis (TB) is a deadly tropical infectious disease caused by Mycobacterium tuberculosis (MTB). The combination of antibiotics as the current TB management raises new problems such as high rates of drug resistance and serious adverse effects on the liver. Alternative therapies that are effective, safe, and affordable in treating TB are needed. Discussion: One of the therapeutic approaches that can be used to avoid bacterial resistance is Host-Directed Therapy (HDT) because it utilizes the host's capabilities. Curcumin is a yellow-colored polyphenol pigment that has a variety of beneficial pharmacological effects including anti-tuberculosis effects through its modulation of the human immune system so that it can be one of the HDTs. However, curcumin still has the major disadvantage of decreased pharmacokinetics because it is easily degraded and its oral bioavailability is poor. To improve its performance, curcumin can be combined with nanoencapsulation agent, chitosan. Curcumin is proven to have the ability to work as Host-Directed Therapy from various studies. Curcumin can inhibit the growth of MTB intracellularly while inducing apoptosis in MTB-infected cells. Nanoencapsulation using chitosan is proven in various trials to improve the pharmacokinetic profile and bioavailability of curcumin so that its performance becomes better. The use of curcumin with chitosan nanoencapsulation in Indonesia is very possible because both agents are very easy to produce domestically and have a relatively affordable price. Conclusion: Nanoencapsulation of herbal curcumin by chitosan has the potential to be an effective, safe, and affordable cutting-edge therapeutic modality in treating tuberculosis in Indonesia. Keywords: HDT, Chitosan, Curcumin, Nanoencapsulation, Tuberculosis